ANALISIS PERBEDAAN KEPUASAN MAHASISWA MENGGUNAKAN MEDIA VIDEO ANIMASI DALAM PEMBELAJARAN KEPERAWATAN GAWAT DARURAT: Comparison of Student Satisfaction Using Animated Video Media in Emergency Nursing Learning - Sudirman, Andi; Sudirman, Andi Aridhasari; Nasrullah; Saini, Sukma; Dwi Anugrah, Firda; Fauziah, Agusti (Media Keperawatan: Politeknik Kesehatan Makassar, 2025)
ABSTRACT Background: Nursing triage education in Indonesia still faces challenges, particularly related to students’ knowledge and satisfaction with the learning process. Less effective learning media, such as PowerPoint, which tends to be static, may affect student engagement and learning outcomes. An innovative alternative is the use of animated video, which provides a more visual, interactive, and engaging learning experience. This study aimed to compare the effectiveness of PowerPoint and animated video on students’ satisfaction in triage nursing education. Methods: This study employed a quasi-experimental design with a pretest-posttest control group approach. The subjects were 36 fifth-semester students of the Diploma in Nursing Program at Poltekkes Kemenkes Makassar, divided into two groups: 18 students in the control group (PowerPoint) and 18 students in the experimental group (animated video). Data were collected using a satisfaction questionnaire before and after the intervention, and analyzed using paired sample t-test and independent sample t-test with a significance level of α = 0.05. Results: The findings showed that student satisfaction in the PowerPoint group increased from a mean of 71.06 ± 4.24 to 71.28 ± 4.32 (p = 0.042). In the animated video group, a greater increase was observed from 71.94 ± 6.88 to 79.38 ± 7.91 (p = 0.018). The comparison of mean differences between groups indicated a significant difference, with the PowerPoint group increasing by only 0.22 ± 0.43, while the animated video group increased by 8.33 ± 7.79 (p = 0.000). Conclusion: Animated video is more effective than PowerPoint in enhancing students’ satisfaction with triage nursing education. It is recommended that nursing education institutions integrate animated videos as innovative learning media to create a more interactive, engaging, and effective learning process. Keywords: Triage Animated video; PowerPoint; Student satisfaction; Emergency nursing education ABSTRAK Pendahuluan: Pendidikan triase keperawatan di Indonesia masih menghadapi tantangan, terutama terkait pengetahuan dan kepuasan mahasiswa terhadap proses pembelajaran. Media pembelajaran yang kurang efektif, seperti PowerPoint yang cenderung statis, dapat memengaruhi keterlibatan mahasiswa dan hasil belajar. Salah satu alternatif inovatif adalah penggunaan video animasi yang menawarkan pengalaman belajar lebih visual, interaktif, dan menarik. Penelitian ini bertujuan untuk membandingkan efektivitas media PowerPoint dan video animasi terhadap kepuasan mahasiswa dalam pembelajaran triase keperawatan. Metode: Penelitian menggunakan desain quasi-eksperimen dengan pendekatan pretest-posttest with control group. Subjek penelitian adalah 36 mahasiswa semester 5 Program Studi D3 Keperawatan Poltekkes Kemenkes Makassar, yang dibagi menjadi dua kelompok: 18 mahasiswa kelompok kontrol (PowerPoint) dan 18 mahasiswa kelompok eksperimen (video animasi). Data dikumpulkan melalui kuesioner kepuasan sebelum dan sesudah intervensi, kemudian dianalisis menggunakan paired sample t-test dan independent sample t-test dengan taraf signifikansi α = 0,05. Hasil: Penelitian menunjukkan bahwa kepuasan mahasiswa pada kelompok PowerPoint meningkat dari rata-rata 71,06 ± 4,24 menjadi 71,28 ± 4,32 (p = 0,042). Pada kelompok video animasi, peningkatan lebih besar terjadi dari 71,94 ± 6,88 menjadi 79,38 ± 7,91 (p = 0,018). Perbandingan selisih rata-rata kepuasan antar kelompok menunjukkan perbedaan signifikan, di mana kelompok PowerPoint hanya meningkat 0,22 ± 0,43, sedangkan video animasi meningkat 8,33 ± 7,79 (p = 0,000). Kesimpulan: video animasi lebih efektif dibandingkan PowerPoint dalam meningkatkan kepuasan mahasiswa terhadap pembelajaran triase keperawatan. Disarankan agar institusi pendidikan keperawatan mengintegrasikan video animasi sebagai media pembelajaran inovatif untuk menciptakan proses belajar yang lebih interaktif, menarik, dan efektif. Kata kunci : Video animasi; PowerPoint; Kepuasan Mahasiswa; Pembelajaran keperawatan gawat darurat